Serum adiponectin levels in patients with rheumatoid arthritis - Ganesh Veluri; Kiranmayi S Vinapamula; P VLN Srinivasa Rao; Sirisha Kommireddy; Suchitra Musturu Manohar; Pullaiah Pasupuleti (Indian Journal of Rheumatology)
Background and Objective: Rheumatoid arthritis (RA) is a chronic inflammatory polyarthritis of common occurrence. Adiponectin is an adipocytokine shown to exert anti-inflammatory as well as pro-inflammatory effects. Our objective was to study the serum adiponectin levels in RA and explore its association with RA disease activity. Materials and Methods: Forty RA patients (newly diagnosed n = 20, RA in clinical remission n = 20) and thirty age-, gender-, and body mass index (BMI)-matched apparently healthy controls were included. Serum adiponectin levels were measured by enzyme-linked immunosorbent assay. RA clinical remission was defined by a Disease Activity Score 28 of <2.6. Results: Serum adiponectin levels were significantly lower in RA patients compared to controls. Both groups of RA patients had lower adiponectin levels than controls. There was no difference in adiponectin levels between the two groups of RA patients. There was no association of adiponectin with disease activity or BMI. Conclusions: Serum adiponectin concentration is decreased in RA patients and was not associated with disease activity.